2021
DOI: 10.3390/ijerph182413181
|View full text |Cite
|
Sign up to set email alerts
|

Is Isocyanate Exposure and Occupational Asthma Still a Major Occupational Health Concern? Systematic Literature Review

Abstract: Isocyanate, whose disease-inducing mechanism is poorly understood, with poor prognosis, is widely used. Asthma is the most frequent manifestation of prolonged exposure. We assessed the evolution of the incidence of isocyanate-induced occupational asthma over time. PubMed and Cochrane databases were systematically searched for studies published since 1990 that assessed the relationship between occupational exposure to isocyanates and asthma. We identified 39 studies: five retrospective cohort studies, seven pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Work duration has been associated with changes in pulmonary function in woodworkers [42], automobile spray painters [43], cement workers [44] and cleaners (sweepers) [45].…”
Section: Work Durationmentioning
confidence: 99%
“…Work duration has been associated with changes in pulmonary function in woodworkers [42], automobile spray painters [43], cement workers [44] and cleaners (sweepers) [45].…”
Section: Work Durationmentioning
confidence: 99%
“…A review reported Scandinavian countries had higher incidence of occupational asthma than Western Europe, United States of America, South Africa, and Brazil [35]. Diisocyanates is the leading cause of occupational asthma in industrialized countries [37], and diisocyanate-related new cases of occupational asthma was estimated to be > 5000/year in the European Union [38]. We showed that people aged 60-64 years old had the highest asthma death and DALYs rate attributed to occupational asthmagens, which was similar with the previous studies [39], and asthma burden remained high after retirement, suggesting cumulative and lagged effect.…”
Section: Discussionmentioning
confidence: 99%
“…For occupational asthma death and DALYs rates, our ndings demonstrated that the period and cohort RRs showed a declining trend in all regions. Promotion of respiratory protection precautions in industry, introduction of sensitive diagnostic methods, and implementation of occupational avoidance could make conspicuous improvement, and thus lead to sharp decrease in the burden of occupational asthma [37]. In 1970, the Occupational Safety and Health Administration was introduced in the USA, and it was the rst occupational regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PU is typically formed by the polycondensation reaction of di/poly-isocyanates and hydroxyl groups in di/polyol; as a result, the urethane functional group is identified in the main chain [9,10]. However, using isocyanate monomers is a non-environmentally friendly and toxic issue, causing serious environmental and human health-related problems, such as irritation of the eyes, respiratory and gastrointestinal tract, and asthma in the long term [11,12]. Therefore, the industrial interest has been shifted to the use of new biodegradable and renewable green resources as PU materials.…”
Section: Introductionmentioning
confidence: 99%